2001
DOI: 10.1111/j.1469-7793.2001.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of adenosine transport by insulin in human umbilical artery smooth muscle cells from normal or gestational diabetic pregnancies

Abstract: Adenosine transport was measured in human cultured umbilical artery smooth muscle cells, isolated from non‐diabetic or gestational diabetic pregnancies, under basal conditions and after pretreatment in vitro with insulin. Adenosine transport in non‐diabetic smooth muscle cells was significantly increased by insulin (half‐maximal stimulation at 0.33 ± 0.02 nm, 8 h) and characterized by a higher maximal rate (Vmax) for nitrobenzylthioinosine (NBMPR)‐sensitive (es) saturable nucleoside transport (17 ± 5 vs. 52 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…8,21,22 Membranes were washed (ϫ6) in Tris buffer saline Tween (TBST, 50 mmol/L Tris/HCl, 150 mmol/L NaCl, 0.02% v/v Tween 20, pH 7.4), and incubated (1 hour) in TBST/0.2% BSA containing horseradish peroxidase-conjugated goat anti-rabbit antibody. Proteins were detected using enhanced chemiluminescence (ECL) detection reagents and quantitated by densitometry using an Ultrascan XL enhanced laser densitometer (LKB Instruments).…”
Section: Western Blot For Enosmentioning
confidence: 99%
“…8,21,22 Membranes were washed (ϫ6) in Tris buffer saline Tween (TBST, 50 mmol/L Tris/HCl, 150 mmol/L NaCl, 0.02% v/v Tween 20, pH 7.4), and incubated (1 hour) in TBST/0.2% BSA containing horseradish peroxidase-conjugated goat anti-rabbit antibody. Proteins were detected using enhanced chemiluminescence (ECL) detection reagents and quantitated by densitometry using an Ultrascan XL enhanced laser densitometer (LKB Instruments).…”
Section: Western Blot For Enosmentioning
confidence: 99%
“…Tracer uptake was terminated by rinsing the monolayers (3 times) with 200 L ice-cold Krebs solution containing 10 mol/L NBMPR, and cell radioactivity was determined by liquid scintillation counting. 6,8 Adenosine transport was also determined in cells exposed to the P 2Y antagonists reactive blue 2 (RB2, 0.1 to 100 nmol/L, 5 minutes or 24 hours), pyridoxal phosphate-6-azophenyl-2Ј,4Ј-disulfonic acid (PPADS, 0.1 to 100 nmol/L, 5 minutes or 24 hours), 20,21 or the G␣ s protein inhibitor 8-(3-benzamido-4-methylbenzamido)-naphthalene-1,3,4-trisulfonic acid (suramin, 100 mol/L, 15 minutes or 24 hours). 22 Cells were then exposed to ATP (0.1 to 100 mol/L, 2 minutes), which is a nucleotide hydrolyzed by ectonucleotidases in human endothelium, 5 ATP-␥-S (0.1 to 100 mol/L, 2 minutes or 24 hours), which is a nonhydrolyzable analogue of ATP, 23 ADP (0.1 to 100 mol/L, 2 minutes), UTP (0.1 to 100 mol/L, 2 minutes), or ␣,␤-methylene ATP dilithium (␣,␤-MeATP, 0.1 to 100 mol/L, 2 minutes), which is a nonselective P 2X purinoceptor agonist, in the absence or presence of RB2, PPADS, or suramin.…”
Section: Adenosine Transportmentioning
confidence: 99%
“…[1][2][3][4] Plasma and tissue levels of adenosine are regulated by an efficient membrane transport mediated by the Na ϩ -independent, nitrobenzylthioinosine (NBMPR)-sensitive equilibrative nucleoside transporter (system es or ENT1) 3,4 in human vascular endothelium 5,6 and smooth muscle. 7,8 Human ENT1 (hENT1) expression in Raji cells (a human B-lymphocyte cell line) is dependent on NO levels and the activity of protein kinase C (PKC). 9 Incubation of human umbilical vein endothelial cells (HUVECs) with 25 mmol/L D-glucose for 24 hours has been reported to reduce the NBMPR-sensitive adenosine transport associated with increased protein levels and the activity of endothelial NO synthase, intracellular Ca 2ϩ , PKC, and mitogen-activated protein kinases p42/p44 mapk .…”
mentioning
confidence: 99%
“…Cell-specific changes in NBMPR-sensitive transport of adenosine in cultured human diabetic cells have been also reported. It was demonstrated that in endothelial cells isolated from human diabetic umbilical vein, NBMPR-sensitive adenosine transport was reduced (Sobrevia et al, 1994), whereas in smooth muscle cells isolated from diabetic human umbilical artery, adenosine transport was significantly elevated (Aguayo et al, 2001). …”
Section: Insulin Effect On Expression Of Nucleoside Transporters 85mentioning
confidence: 99%